Understanding marital violence: a study in grounded theory - Jordana Brock Carneiro; Nadirlene Pereira Gomes; Luana Moura Campos; Andrey Ferreira da Silva; Kamylla Santos da Cunha; Dália Maria De Sousa Conceição Da Costa
Objective: to understand the phenomenon of marital violence based on the experience of women in judicial process and network professionals. Method: a qualitative study, with theoretical-methodological support in grounded theory. Data collection took place in two regional Courts for Peace in the Home in a municipality of the Brazilian Northeast. Interviews were conducted with 38 participants, who composed two sample groups: women in situations of violence and network professionals. Results: the understanding of marital violence emerged for the phenomenon "Experiencing marital violence as a progressive and cyclical process, with repercussions for health and implications for social relations". Conclusion: in recognizing marital violence as a recurring problem in the life of women, with implications for their own health and that of their children, the study points to the relevance of coping strategies based on institutional and social support.